Advanced Data Assimilation for Geosciences - Edited by Blayo, E. et.al (Oxford Oxford University Press, 2015)
This book gathers notes from lectures given during a three-week summer school on the fundamentals and the most recent developments of geophysical data assimilation.
Including Illustrations and Graphs
Keywords: Earth sciences--Data processing -- Earth sciences--Mathematical models